Cerebral Salt Wasting Syndrome pada Pasien dengan Infark Serebri : Sebuah Laporan Kasus - Hapsari, Aulia; Prakoso, Budi (RSUD Dr. Saiful Anwar Province of East Java, 2023)
Background: Hyponatremia is a common problem in hospitals, especially among patients suffering from central nervous system disorders., it is frequently caused by SIADH (Syndrome Inappropriate Antidiuretic Hormone) and CSWS (cerebral salt wasting syndrome). Case Report: A 71-year-old woman presented with complaints of not being conscious for 12 hours before the admission and a history of slipped and hit her head on the floor three days prior to admission. The patient has a history of hypertension and is currently taking 5 mg of amlodipine. With severe hyponatremia, the patient appeared dehydrated and had a urine output of 3000cc/day. The patient was diagnosed with CSWS and was given hypertonic saline and steroids. Patients respond positively to the therapy, as evidenced by regular increases in serum sodium levels and regain of consciousness. Discussion: CSWS is a hyponatremia and dehydration condition caused by a head injury, cerebral infarction, or other neurological disorders. The cause of CSWS is influenced by natriuretic peptides, which are released not only in conditions of heart failure but also in conditions of central nervous damage. Conclusion: In this case report, a 71-year-old woman with CSWS caused by a cerebral infarction responded favourably to hypertonic saline and steroid therapy. In order to provide holistic and comprehensive therapy, the condition of hyponatremia must be defined for the main cause, notably SIADH or CSWS, which is obtained from the history taking to supporting examinations.